Keeping my Mandarin alive : Lee Kuan Yew's language learning experience - Lee, Kuan Yew, 1923-2015 (World Scientific : Global Pub., 2005)
Learn Mandarin while you brush your teeth or shave? Read how Singapore's Minister Mentor Lee Kuan Yew does it! A Prime Minister as an interpreter? Find out when and why MM Lee had to do it. For the first time, this towering figure of the island-state's politics gives a first-hand account of How he has learnt Mandarin over the last 50 years and kept it alive. He also tells When and Why he decided to learn the language, Where he got hold of the learning materials from, Whom he practises his Mandarin with and What spurs him on. MM Lee goes beyond these 5Ws and 1H in Keeping My Mandarin Alive, to share the agony of a mature Chinese language student and how he has overcome the difficulties - he strove to learn Mandarin only at age 32 (from 1955) and Hokkien at age 38 (from 1961). The comprehensive package also details how the English-educated MM Lee has been relating Mandarin to his master language in an effort to grasp the former and unravels how the latest technology has helped him in his quest. Edited by Dr Chua Chee Lay, one of MM Lee's Chinese tutors, Keeping My Mandarin Alive comprises : a book detailing his lifelong pursuit peppered with interesting photographs and comments from his Chinese language tutors; a DVD-Rom featuring snippets of an exclusive interview with Lee Kuan Yew and a demo version of the software he has been using to learn Mandarin; samples of materials that Lee Kuan Yew has been using to pick up the language; a guide on what resources (Chinese software, useful websites and dictionaries, among others) one can tap on to learn Mandarin. This book is also available in Chinese.